2019
DOI: 10.1007/s00420-019-01495-4
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured versus self-reported occupational physical activity and multisite musculoskeletal pain: a prospective follow-up study at 20 nursing homes in Denmark

Abstract: Purpose To explore the prospective association of objectively measured and self-reported occupational physical activity (OPA) with multisite musculoskeletal pain (MSP) among Danish eldercare workers. Methods The study population consisted of eldercare workers in 20 Danish nursing homes (N = 553, response rate 59%, 525 female). Baseline data were collected in 2013-2014 and the 1-year follow-up was completed in 2016. At baseline, we measured objective OPA by a thigh-worn ActiGraph GT3X + accelerometer during wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…27 28 With objective measurements there were no associations between resident handling in eldercare and risk of low back pain over 1 year. 29 Physical exposures have probably been overstated as potential causes of MSK pain and the results from the CUPID study found that differences in general propensity to MSK pain is a major driver of large international variation in the prevalence of MSK pain among people of working age, and that we must look for the causes of general propensity to MSK pain. Coggon has suggested that ‘Much more plausible is the possibility that culturally determined differences in health-related beliefs and behaviours in some way modify awareness of, and responses to, pain; perhaps through changes in the central processing of sensory information’.…”
Section: Discussionmentioning
confidence: 99%
“…27 28 With objective measurements there were no associations between resident handling in eldercare and risk of low back pain over 1 year. 29 Physical exposures have probably been overstated as potential causes of MSK pain and the results from the CUPID study found that differences in general propensity to MSK pain is a major driver of large international variation in the prevalence of MSK pain among people of working age, and that we must look for the causes of general propensity to MSK pain. Coggon has suggested that ‘Much more plausible is the possibility that culturally determined differences in health-related beliefs and behaviours in some way modify awareness of, and responses to, pain; perhaps through changes in the central processing of sensory information’.…”
Section: Discussionmentioning
confidence: 99%
“…These questions have not been validated using objective measures or larger validated questionnaires, respectively. However, related studies show that single-item measures of physical activity are robust predictors of health outcomes, 37 and previous studies using HPI data have demonstrated the predictive validity of these single-item questions. 38 Alcohol consumption was assessed using AUDIT-C (first 3 items).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, one would expect that in the epidemiology of work‐related musculoskeletal disorders—conditions which have a high spontaneous incidence even in non‐exposed populations—case definitions were based on the best available diagnostic techniques, exposures were directly measured with an appropriate tool and studies were performed with blind techniques (exposure/outcome) 40 . In addition to that, direct measurements and video‐based observation of exposure are more desirable considering that these methods are assumed to have a higher level of accuracy than subjective assessment and self‐reports, which tend to be more prone to misclassification of the exposure 44,45 …”
Section: Discussionmentioning
confidence: 99%